Gait pattern alterations in older adults associated with type 2 diabetes in the absence of peripheral neuropathy - Results from the Baltimore Longitudinal Study of Aging - Ko, Seung-uk (2011)
Diabetes may impact gait mechanics before onset of frank neuropathies and other associated threats to mobility. This study aims to characterize gait pattern alterations of type 2 diabetic adults without peripheral neuropathy during walking at maximum speed (fast-walking) as well as at self-selected speed (usual-walking). One-hundred and eighty-six participants aged 60 to 87 from the Baltimore Longitudinal Study of Aging (BLSA) able to walk unassisted and without peripheral neuropathy were classified as non-diabetic (N = 160) or having type 2 diabetes (N=26). Gait parameters from the fast-walking and usual-walking tests were compared between participants with and without type 2 diabetes. Participants with diabetes had a shorter stride length for fast-walking (p = 0.033) and a longer percentage of the gait cycle with the knee in 1(st) flexion for both fast- and usual-walking (p = 0.033, and 0.040, respectively) than non-diabetic participants. Participants with diabetes exhibited a smaller hip range of motion in the sagittal plane during usual-walking compared to non-diabetics (p = 0.049). During fast-walking, participants with diabetes used lower ankle generative mechanical work expenditure (MWE) and higher knee absorptive MWE compared to non-diabetic persons (p = 0.021, and 0.018, respectively). These findings suggest that individuals with type 2 diabetes without overt peripheral neuropathy exhibit altered and less efficient gait patterns than non-diabetic persons. These alterations are more apparent during walking at a maximum speed indicating that maximum gait testing may be useful for identifying early threats to mobility limitations in older adults with type 2 diabetes.